Minoritas dalam Minoritas: Agensi Religius dalam Penutupan Tempat Ibadah Jemaat Gereja Bethel Indonesia di Langsa, Aceh - Muhammad Ansor (Raudhatun Najah Publisher, 2023)
This article examines the Indonesia Bethel Church (GBI, Gereja Bethel Indonesia) in Langsa, Aceh, Indonesia. Based on the concept of a religious agency, the article explores how the Langsa GBI community treats religious beliefs in the midst of interest after the sealing of private places of worship that are considered to be churches by the town government of Langsa. Qualitative data was collected through participatory observations, semi-structured interviews and focus group discussions to members of the GBI community in Langsa conducted arround the course of 2015-2021. The author also interviewed Christians outside of the GBI members as well as Muslims in the research area to explore their constructions towards the topics discussed. This paper finds fragmentation of the religious agency of the GBI in Langsa in an effort to practice and treat believed religious doctrines when faced with interests or critical situations. The status of a minority within the minority and the way they represent the situation influence the articulation of religious agency.